Recent discoveries and developments of androgen receptor based therapy for prostate cancer. Issue 5 (13th May 2015) - Elancheran, R.; Maruthanila, V. L.; Ramanathan, M.; Kabilan, S.; Devi, R.; Kunnumakara, A.; Kotoky, Jibon
<x xml:space="preserve">Abstract</x> The main focus of this review is to discuss the discoveries and developments of various therapies for prostate cancer.